Papel da hidrografia e do clima na estrutura genética do roedor semiaquático Nectomys squamipes - Dalapicolla, Jeronymo (2014)
Nectomys squamipes (Rodentia: Sigmodontinae) is a semiaquatic rodent that occurs in Neotropical forests of eastern South America. Low levels of gene flow and strong genetic structure were expected among populations of this species due to its close association with aquatic environments and its small home range. Published studies, however, showed the opposite—a strong genetic homogeneity in populations of this species. The aim of the present study was to investigate why N. squamipes shows this genetic homogeneity, considering the roles of gene flow, hydrography and Pleistocene climatic oscillations. Using 167 tissue samples of N. squamipes from eastern Brazil, I sequenced two mitochondrial markers: cytochrome b (Cyt b) and D-loop. Based on 108 localities and ecological niche modeling, I inferred environmental suitability maps using climatic envelopes of the present and the past. Molecular results showed a shallow genetic structure that is consistent with hydrography. I found few differences in environmental suitability when comparing the Last Glacial Maximum (21,000 years ago) to the present, but major changes when compared to the Last Interglacial period (130,000 years ago). The combination of genetic and ecological results allowed the reconstruction of gene flow routes based on watershed connections among Atlantic Forest rivers. The current genetic structure in Nectomys squamipes results from the combination of gene flow within and among basins, and recurrent population contractions and expansions during the Quaternary climatic oscillations